Análisis a los Estados Financieros a la Empresa AUTOSHOPPING del Señor Juan Andrés Echeverria Cuadros, de la ciudad. de Loja. Periodo 2020 - 2021. - Cevallos Contento, Silvia Beatriz (2023)
The present research work called ANALYSIS OF THE FINANCIAL STATEMENTS OF THE COMPANY AUTOSHOPPING OF MR. JUAN ANDRES ECHEVERRIA CUADROS, OF LOJA CITY, PERIOD 2020 - 2021, it allowed to identify the financial management to take decisions with the purpose to know the economic and financial situation of the company so that it enables the manager to make the right decisions at the right time and also it was carried out in accordance with the requirement prior to obtain the degree and title of Engineer in Accounting and Auditing, Certified Public Accountant-Auditor at the National University of Loja. In addition, in order to carry out and complete the first objective, it was necessary to gather the financial information to obtain, analyze the economic and financial structure and thus to determine the participation of each of the accounts regarding the group and subgroup and identify the increase and decrease observed from one period to another, therefore it was observed a greater investment in the current assets, where the most relevant account is Inventories for the year 2020 which had a value of $752,190.23 equivalent to 52%, while in the year 2021 it has a value of $975.719,56 equivalent to 69.92%, results that correspond to the main activity of the company, sale of merchandise; it was observed that the account with the greatest increase was Cash and Cash Equivalents with an increase of $14,884.80, which represents 66.19%, as a result of the increase in sales of spare parts and accessories for vehicles in cash. On the other hand, in order to complete the second objective, it was applied the financial indicators that they are used in commercial companies to determine the levels achieved against the established standards, which allowed to measure the performance of the company, through the liquidity indicator it was determined that the company has sufficient capacity to cover its short-term obligations; the activity indicator shows that the company is efficient in the use of resources such as inventories, portfolio and suppliers, where the portfolio turnover in 2020 and for the year 2021 it takes approximately 5 months, this is not acceptable because it shows that customers are not paying their credit in the established terms; the indebtedness indicator shows that the company is indebted by an average of 85%, which means that it is reducing its financial autonomy, because its creditors are practically the owners of the company. Finally, in order to complete the last objective, a report on the financial analysis was prepared with conclusions and recommendations, which is provided to the company's manager so that he can make the necessary changes to improve the company's management.